Measures of constitutional legal enforcement in the constitutional law of Brazil - Irina A. Tretyak (Правоприменение)
The subject. The article is devoted to different measures of constitutional legal enforcement in the constitutional law of Brazil, their analyzing, depending on main goal of coercion.The purpose of the paper is to extend constitutional knowledge about measures of constitutional legal enforcement and to demonstrate generic character of constitutional legal enforcement theory for different countries.The methodology of the study includes general scientific methods (analysis, synthesis, description) and legal methods.The main results and scope of their application. The author describes different measures of constitutional legal enforcement in the constitutional law of Brazil. Constitutions of foreign countries contain various measures of constitutional coercion as the main way to resolve constitutional conflicts.Among the measures of constitutional and legal coercion enshrined in the Brazilian Constitution are: holding the President accountable for abuse of power; temporary termination of the powers of the President of the Republic during the process of bringing him to justice; prohibition of the President and Vice-President of the Republic to leave the territory of the country for a certain period without the approval of the Parliament; recognition by the National Congress of the positions of the President and Vice-President as vacant if they fail to exercise their constitutional powers within 10 days of taking office;holding new elections when the positions of the President and Vice-President are declared vacant if they fail to exercise their constitutional powers within 10 days from the date of taking office.Conclusions. Depending on the constitutional system, the history of the state, measures of constitutional coercion may be different in content, but it remains possible to classify such measures depending on the main purpose of their application. The system of measures of constitutional legal enforcement, including measures of prevention, suppression, restoration, responsibility and security is applicable not only for the Russian constitutional law, but also for constitutional law of foreign countries, in particular, Brazil.